Implementasi Pencarian Sekuensial Pada Sistem Informasi Administrasi Gereja Katolik Gembala Baik Pontianak - Giovanna, Aurelyn; Willay, Thommy; Antonius, Antonius (Universitas Multi Data Palembang, 2025)
This Research aims to develop an administrative system to facilitate the sacrament registration process for baptism candidates by utilizing website. At Gembala Baik Catholic Church in Pontianak, the current administrative system is not well-integrated, making data retrieval for parishioners and baptism candidates time-consuming and leading to complaints about the church’s administrative services. This research employs a qualitative method for data collection and a sequential method for data retrieval. A well-integrated administrative system will provide a strong foundation for the church’s growth and positively impact its services to the congregation. The use of the sequential method in data retrieval offers a faster and ordered data processing without excessive data load.